Photosensitizer Micelles Together with IDO Inhibitor Enhance Cancer Photothermal Therapy and Immunotherapy. Issue 5 (26th February 2018) - Peng, Jinrong; Xiao, Yao; Li, Wenting; Yang, Qian; Tan, Liwei; Jia, Yanpeng; Qu, Ying; Qian, Zhiyong
Abstract: The therapeutic outcome of photothermal therapy (PTT) remains impeded by the transparent depth of light. Combining PTT with immunotherapy provides strategies to solve this problem. Regulating metabolism‐related enzymes is a promising strategy to stimulate immune response. Here, a nanosystem (NLG919/IR780 micelles) with the properties of photothermal conversion and regulation of the tryptophan metabolic pathway is used to suppress the growth of the tumor margin beyond effective PTT and promote tumor PTT and immunotherapy. It is revealed that mild heat treatment promotes the growth of the tumor margin beyond effective PTT for the upregulation of heat shock protein (HSP), indoleamine 2, 3‐dioxygenase (IDO), and programmed death‐ligand 1 (PD‐L1). The NLG919/IR780 micelles can effectively inhibit the activity of IDO but do not affect the level of IDO expression. NLG919/IR780 micelles can effectively accumulate in the tumor and can migrate to lymph nodes and the lymphatic system. In vivo antitumor studies reveal that NLG919/IR780 micelles effectively suppress the growth of tumor margin following PTT in primary tumors. NLG919/IR780 micelle‐mediated PTT and IDO inhibition further stimulate the activation of T lymphocytes, inhibiting the growth of distal tumors (abscopal effect). The results demonstrate that the NLG919/IR780 micelles combine PTT and immunotherapy and suppress the tumor margin as well as distal tumor growth post photothermal therapy. Abstract : During photothermal therapy (PTT), the tumor margin beyond effective PTT is upregulating series proteins, including indoleamine 2, 3‐dioxygenase (IDO), and programmed death‐ligand 1 (PD‐L1) which further accelerate the growth of tumors. By combining with IDO inhibitor, the therapeutic outcome of PTT is enhanced, which also triggers strong immune response to alleviate metastasis and the growth of distant tumor.